2015
DOI: 10.1158/0008-5472.can-14-2467
|View full text |Cite
|
Sign up to set email alerts
|

TLR5 Ligand–Secreting T Cells Reshape the Tumor Microenvironment and Enhance Antitumor Activity

Abstract: The tumor microenvironment counters antitumor T cell responses in part by blunting their activation and infiltration. Ligands that engage Toll-like receptors (TLR) on T cells and antigen-presenting cells can act as potent immune adjuvants. In this study, we show how tumor-reactive T cells engineered to secrete bacterial flagellin, a TLR5 ligand (TLR5L), can engender a co-stimulatory signal that augments antitumor activity. Human T cells engineered to express TLR5L along with DMF5, a T cell receptor that recogn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 54 publications
(68 reference statements)
0
27
0
Order By: Relevance
“…Genes were cloned into the pMIG-w vector containing a GFP reporter gene. Retroviral vector supernatants were produced from Phoenix Ampho and Eco packaging cell lines we have previously described(11). For generating engineered mouse T cells, pmel or OT-I T cells were activated for 48 hrs.…”
Section: Methodsmentioning
confidence: 99%
“…Genes were cloned into the pMIG-w vector containing a GFP reporter gene. Retroviral vector supernatants were produced from Phoenix Ampho and Eco packaging cell lines we have previously described(11). For generating engineered mouse T cells, pmel or OT-I T cells were activated for 48 hrs.…”
Section: Methodsmentioning
confidence: 99%
“…rhLYG1-induced upregulation in the expression of chemokines within tumors is associated with increased T-cell infiltration and antitumor response, which is consistent with the previous studies. 30,31 Our data showed that LYG1 could increase the chemokine secretion in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 70%
“…Such stimulation decreased tumor volume in models of breast cancer , colorectal cancer (Rhee et al, 2008), lung cancer (Burdelya et al, 2012;Zhou et al, 2012), and T-and B-cell lymphoma (Leigh et al, 2014), mainly mediated by increased tumor necrosis and neutrophil infiltration Rhee et al, 2008;Zhou et al, 2012). In addition, in a melanoma mouse model, T cells engineered to constitutively produce TLR5 ligand could increase anti-tumor activity by increasing proliferation and cytolytic activity of these T cells against melanoma cells (Geng et al, 2015). Finally, in a cohort of patients with non-small-cell lung cancer (NSCLC), TLR5 overexpression was associated with good prognosis.…”
Section: Anti-tumoral Effectmentioning
confidence: 99%